Penguatan Kemampuan Interaksi Sosial Anak Melalui Praktik Bermain Tradisional di TK Dewi Sartika Gondang - Musafir, Musafir; Muhajirin, Muhammad; Hamdani, Muh.; Prisma Mahendra, Juandra; Puspa Sari, Titik; Pasigar, Andi (Jurnal Pengabdian Masyarakat Sains Indonesia, 2021)
This service discusses strengthening children's social interaction skills through traditional playing practices, especially the game of hide and seek, at Dewi Sartika Gondang Kindergarten. Traditional games are recognized as an effective means of developing children's social, emotional and cognitive skills. Through this service, we identified the positive impact of traditional play practices on children's social interactions, as well as how this can be integrated into the early childhood education curriculum. From the results of the game of hide and seek, it has proven to be effective in strengthening children's social interaction skills at Dewi Sartika Gondang Kindergarten. Through this play, children not only learn to communicate and cooperate, but also develop important cognitive and emotional skills. This dedication emphasizes the importance of integrating traditional games in the early childhood education curriculum to support holistic social development